PERSONAL INTEREST, OVERCONFIDENCE, DALAM MENINGKATKAN KEPUTUSAN INVESTASI DENGAN LITERASI KEUANGAN SEBAGAI VARIABEL MODERASI - Intani, Sri; Sartika, Dewi (Jurnal Ekonomi Manajemen, 2024)
This research aims to determine the influence of personal interest and overconfidence on investment decisions which are moderated by financial literacy. The population in this study were students at Bina Darma University, Palembang, with a sample size of 92 respondents. The data collection technique uses a questionnaire and then analyzed using SEM-PLS with the help of SmartPLS software. The research results show that Personal Interest influences investment decisions, Overconfidence influences investment decisions, Financial literacy cannot moderate the relationship between Personal Interest and investment decisions, Financial literacy cannot moderate the relationship between Overconfidence and investment decisions